The Possibility to Reuse Nanocomposite Industrial Wastes for Asphalt Binder Modification Technology - Temesgen, Sagni; Garedew, Girmaye; Jirata, Leta (Trends in Sciences, 2022)
A nanocomposite solid waste polymer has been used for increasing the durability of pavements that the softness of asphalt binder drops seriously at high temperature. The research is concerned with the possibility of utilizing locally available materials as an ingredient in asphalt concrete to enhance pavement performance, increase the mixture engineering property and at the same time decreasing the amount of bitumen required. The experimental work includes characterization of bitumen by using super pave tests (Dynamic Shear Rheometer) for both neat and modified bitumen. In this specific investigation the wet process is used for introducing the Portland cement, ceramic dust and Hydrate lime into bitumen during a modification process. Overall, 3 specimens with, 3 modifiers together with content 0 (neat bitumen), 1.5, 3.0 and 4.5 % by weight of asphalt binder were prepared. By considering the results generated from Dynamic Shear Rheometer (DSR); the isochronal plots indicates that a neat asphalt binder modified with composite of Portland cement, hydrate lime and ceramic dust resulting in the decreasing phase angle value and at the same time increasing the stiffness modulus of bitumen. This indicates that, on the 1 side, better stiffness and elastic behavior that the asphalt binder can directly suit for higher stability to resist rutting, hence, bitumen performance was upgraded with content of modifiers increased. On the other side, the heat insulation effect of the Portland cement, hydrate lime and ceramic dust will improves the temperature susceptibility of the asphalt binder which corresponds to permanent deformation resistance. HIGHLIGHTS One of the common problem is temperature susceptibility of asphalt binder resulting permanent deformation at hot climate area Portland cement, ceramic dust and hydrate lime modifiers mixed together with different contents into asphalt binder during a modification process in order to find out asphalt binder which corresponds to rutting resistance Increased stiffness modulus and decreased phase angle values has been achieved as a content of modifiers increased and the heat insulation effects of the modifiers will improves the temperature susceptibility of asphalt binder GRAPHICAL ABSTRACT